Sharp bounds for the extreme zeros of classical orthogonal polynomials - Dimitrov, Dimitar Kolev [UNESP]; Nikolov, Geno P. (Academic Press Inc. Elsevier B.V., 2010)
Bounds for the extreme zeros of the classical orthogonal polynomials are obtained by a surprisingly simple method. Nevertheless, it turns out that, in most cases, the estimates obtained in this note are better than the best limits known in the literature. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Extreme zeros; Classical orthogonal polynomials; Sharp bounds